An increase in the competitiveness of industrial enterprises in the process of developing innovation practices / Konkurencingumo didinimas ortopedijos pramonės įmonėse plėtojant inovacinę veiklą - Paulius Slavinskas (Mokslas: Lietuvos Ateitis, 2012)
The article presents research on increasing competitiveness based on the development of innovative activity in the medium-sized enterprises of orthopaedic industry. The paper analyzes the theoretical and practical aspects of improving competitiveness and innovation development on the basis of which a model for increasing competitiveness using innovative products in orthopaedic industry has been formed and proposed. The article also describes the components of the proposed model and assesses the possibility of applying it in practice.